The Effect of Macroeconomic, Microeconomic, and Systematic Risk on Firm Value in the Jakarta Islamic Index 30 (JII30) - Hilmi, Muhammad Irfan; Desmiza (Indonesian Scientific Publication, 2025)
This research examines the influence of macroeconomic, microeconomic, and systematic risk factors on firm value inside the Jakarta Islamic Index 30 (JII30) from 2019 to 2023. The imperative is to comprehend investor perception in Sharia-compliant capital markets, where investment choices are influenced by ethical standards and a long-term perspective. This study analyzes inflation and interest rates (macroeconomic factors), ROE and TATO (microeconomic indicators), and beta (systematic risk), chosen for their significance in indicating corporate performance and investor appeal. The population comprises 52 companies listed in the JII30 during 2019–2023. Using purposive sampling, 21 firms were selected, producing 105 observations. Data were analyzed through panel data regression with the Random Effect Model (REM), determined by the Chow, Hausman, and Lagrange Multiplier tests. Results show that all variables simultaneously have a significant effect on firm value, while only ROE and TATO individually have a significant positive influence. Inflation, interest rates, and beta are insignificant. These findings indicate that Sharia investors focus more on internal performance, such as profitability and asset efficiency, rather than reacting to short-term macroeconomic changes. Practically, management should prioritize strategies that enhance efficiency and profitability, while regulators can encourage transparent disclosure of internal performance indicators to sustain investor trust and support long-term market stability.